Developing Learning For Children With Special Needs In Inclusive Education Through Mitra Bimbing Learning Model - Abdullah, Mulyana (International Journal Pedagogy of Social Studies, 2018)
A teacher as educators, is required to create a system environment or conducive conditions so that learning activities can achieve its goals effectively and efficiently. Thus, it is necessary to determine learning approach that would be used to establish a strategy or model of learning as a conceptual framework that describes a systematic procedure in organizing the learning experience of learners to achieve specific learning and serve as guidance to designers of learning and teachers in planning and implementing activities of teaching and learning. Basically, the implementation of strategies and models of learning for learners who have normal physical and psychological conditions can be said easy for experienced educatorsÂ  to implement. Various models of learning can be implemented smoothly and finely. Different with learning that cater learners with special needs. Model and learning strategies for students with this category need to consider various aspects of their physical and psychological, considering they have a deficiency in them, both in terms of physical, psychological, intellectual, and emotional. This is where the design of â€œMitra Bimbingâ€ learning model for children with special needs become one of the alternative. This design of Mitra Bimbing learnig model for children with special needs shows that there has been three phases of learning which it should be applied in more integrated, which is concentrating students to one learning domain that they can rich, encouraged students feeling or revealing his opinion freely, so that it wouldnâ€™t there is an impression impose the students to acquire something, but it develop their ability onÂ their own, show the common examples or analogy that was familiar for them which deals with the material is being studied. In practice, the Mitra Bimbing learning model cannot be separated from many factors that influence it, which is teachers involvement directly who have basic of special education, either in planning or implementing and evaluating of learning, the availability of adequate learning facilities and infrastructure for children with special needs,Â  and the attention and awareness of from the government, parents, community, and stakeholdersÂ to the efforts of special needs education